Dexmedetomidine as a Single Bolus Dose in Laparoscopic Cholecystectomy under General Anesthesia – A Comparison of Different Doses - Pyakurel, Kumud; Rajbanshi, Lalit Kumar; Thapa, Chitra; Regmi, Gunjan (Birat Journal of Health Sciences, 2020)
Introduction: Dexmedetomidine has an ideal pharmacodynamic profile for attenuation of stress response during general anesthesia for laparoscopic cholecystectomy. Since, the value of dexmedetomidine as a single premedication dose remains largely unexplored, this study compared dexmedetomidine in 0.5μg/kg and 1μg/kg dose for laparoscopic cholecystectomy under general anesthesia. Objectives: The primary objective of this study was to compare dexmedetomidine in a single premedication dose of 0.5μg/kg and 1μg/kg in terms of hemodynamic (heart rate and mean arterial pressure) changes to critical incidences such as laryngoscopy, endotracheal intubation, pneumoperitoneum and extubation. The secondary objectives were to compare induction dose of propofol required, sedation scores in the immediate post anesthesia period and adverse events such as bradycardia and hypotension. Methodology: This was a prospective double blind study. Ninety-two patients aged 18-55 years of either gender of American Society of Anesthesiologists physical status I-II were randomly allocated into two groups to receive either Dexmedetomidine 1μg/kg or 0.5μg/kg slowly IV over 10 minutes as a premedication before induction. Heart rate, Mean arterial pressure, induction dose of propofol, sedation scores, and adverse events were compared. Results: The patient characteristics, Fentanyl consumption, duration of surgery and anesthesia in both groups were comparable. There was comparable attenuation of hemodynamics in both groups during laryngoscopy and intubation. Dexmedetomidine in 1μg/kg compared to 0.5μg/kg had significantly better attenuation of hemodynamics from 1 minute to 40 minutes of pneumoperitoneum. After 40 minutes, there was no attenuation in either group. The post anesthesia sedation scores were comparable. The induction dose of propofol was significantly less and the incidence of bradycardia was significantly higher with dexmedetomidine 1μg/kg. Conclusion This study demonstrates that a premedication dose of Dexmedetomidine in 1μg/kg compared to 0.5μg/kg has significantly betier attenuation of hemodynamics from 1 minute to 40 minutes of pneumoperitoneum.